An Analysis of the Nature of Young Students' STEM Learning in 3D Technology-Enhanced Makerspaces. Issue 1 (2nd January 2021) - Forbes, Anne; Falloon, Garry; Stevenson, Michael; Hatzigianni, Maria; Bower, Matt
ABSTRACT: Research Findings : This study was undertaken to investigate learning processes and outcomes from using 3D design and printing technologies with children aged 5–8 years, in three schools in a metropolitan city in Australia. Data were collected from five sources (teacher interviews, surveys, journals; student interviews; and iPad screen recordings) and analyzed to identify themes responding to the question: What is the nature of students' learning and learning processes in technology-enhanced Makerspaces? Findings report the perspectives of teachers and students, supplemented by screen recordings from the iPads. Students were found to have significant engagement in learning through involvement in these technology-enhanced Makerspaces, and to have developed skills and understanding in a number of areas including: digital technical proficiency, design thinking, problem solving, critical thinking, collaboration, and communication. Findings are conceptualized using a research-informed Maker Literacies Framework, to better understand the nature of students' learning and work processes while engaged in these environments. Practice or Policy: Findings imply that Makerspaces with 3D design and printing could be used to promote young children's STEM literacies although teachers need to be mindful of the need to explicitly plan for and teach important STEM concepts, if learning in these disciplines is a goal.